Implementasi Metode Key Performance Indicator (KPI) dalam Pengukuran Kinerja Receptionist Di Amadea Resort & Villa Seminyak - AAA Ribeka Martha Purwahita purwahita; I Ketut Saskara; Ni Ketut Sutrisnawati (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2023)
The Key Performance method is used to measure employee performance and is implemented for receptionists at Amadea Resort & Villas Seminyak. The overall results of receptionist performance measurements at Amadea Resort & Villas Seminyak are based on assessment criteria with a method called key performance indicators to measure overall performance, carried out according to predetermined standards. This study uses a qualitative descriptive approach, including observation, interviews and document review at the receptionist at Amadea Resort & Villas Seminyak. Determination of respondents using total sampling method. The KPI (Key Performance Indicator) assessment criteria at Amadea Resort & Villas Seminyak are excellent Service, Upselling Revenue, Guest Recommendation, Training, Perfect Grooming and Perfect Attendant. Keywords: key performance indicator method, performance measurement, receptionist